2006
DOI: 10.3748/wjg.v12.i40.6540
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of hepatitis B virus isolates in Mexico: Predominant circulation of hepatitis B virus genotype H

Abstract: HBV genotype H is highly predominant in HBV isolates of Mexico followed by genotypes G, A and D. A low frequency of precore and core promoter mutations is observed in HBV Mexican isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…HBV genotype G has been reported in Asian, American, and western European countries [Shibayama et al, 2005; Alvarado‐Esquivel et al, 2006; De Maddalena et al, 2007; Jardi et al, 2008]. The present study identifies HBV genotype G as a minor genotype.…”
Section: Discussionsupporting
confidence: 65%
“…HBV genotype G has been reported in Asian, American, and western European countries [Shibayama et al, 2005; Alvarado‐Esquivel et al, 2006; De Maddalena et al, 2007; Jardi et al, 2008]. The present study identifies HBV genotype G as a minor genotype.…”
Section: Discussionsupporting
confidence: 65%
“…The presence of HBV/A significantly increases the rate of HBV/G replication in hepatocytes, although infection with HBV/G alone is possible. [46][47][48][49] Genetic rearrangements between HBV/A and HBV/G can occur during persistent coinfection. Therefore, we examined how novel Ae/G recombinants were generated and transmitted in the Japanese MSM population.…”
Section: Discussionmentioning
confidence: 99%
“…HBV/H is also considered an Amerindian genotype, as it is found in Central America, primarily in Mexico and Nicaragua [9,40]. Since HBV/F and HBV/H are closely related, it has been suggested that these genotypes likely split off from each other within the New World, via division of an ancestral HBV strain carried by the first settlers that entered the continent across the Bering Strait around 15,000 years ago [9,41].…”
Section: Discussionmentioning
confidence: 99%